2004
DOI: 10.2176/nmc.44.225
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Management of Intracranial Hemorrhage in Patients Undergoing Maintenance Dialysis Therapy

Abstract: The management and outcome were retrospectively investigated in patients with chronic renal failure receiving maintenance blood purification who suffered intracranial hemorrhage. Patients with intracerebral hemorrhage (ICH, n = 36) or subarachnoid hemorrhage (SAH, n = 5) were evaluated. Both groups were initially managed using continuous hemofiltration (HF) after admission, except for two patients with SAH receiving maintenance peritoneal dialysis. Patients with ICH were managed with HF three times a week afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
(23 reference statements)
1
20
1
Order By: Relevance
“…[11,12] Little is known about the exact mechanism. It is assumed, however, that the decreased effect of a serine protease inhibitor on the hematoma, as seen in the current study, is associated with the suppressing effect on vasoconstriction occurring as the secondary phenomenon in the acute phase following the onset of cerebral bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Little is known about the exact mechanism. It is assumed, however, that the decreased effect of a serine protease inhibitor on the hematoma, as seen in the current study, is associated with the suppressing effect on vasoconstriction occurring as the secondary phenomenon in the acute phase following the onset of cerebral bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the mortality rates were not significantly different for the EHD and CPD patients. In addition, our patients had a relatively lower mortality rate (total mortality 27.9%) than other series (mean mortality 62.1%, range 43.8–67.3%) [7,8,10,11,16,17,18]. The mean outcome score was 3 in the CPD and 2 in the EHD groups, respectively.…”
Section: Discussionmentioning
confidence: 48%
“…The prognosis of ICH in chronic dialysis patients is especially poor. The 30-day mortality rate has been reported to be as high as 67.3% (range 43.8–67.3%) [7,8,10,11,16,17,18]. The total 30-day mortality rate of our patients was 27.9%.…”
Section: Discussionmentioning
confidence: 55%
“…10,22) The prognosis for HD patients with large cerebral hematoma is poor. 18) The systolic and diastolic blood pressures before and after HD were significantly higher in the intracerebral hemorrhage group than in the control group. 13) History of hypertension and elevated diastolic pressure after the initial stroke are associated with increased risk of second stroke.…”
Section: Discussionmentioning
confidence: 80%
“…11,22,23) Management of intracerebral hemorrhage in HD patients is complicated by factors such as: hypotension during dialysis; active bleeding and coagulopathy that may be exacerbated by the systemic anticoagulant therapy used in HD; and dialysis disequilibrium syndrome. 18) The mortality of HD patients with intracerebral hemorrhage is nearly two times higher than that in non-HD patients. 22) Therefore, investigation of the predictors of intracerebral hemorrhage is important.…”
Section: Introductionmentioning
confidence: 99%